Validation of the preference-based multiple sclerosis index. (October 2019) - Kuspinar, Ayse; Mayo, Nancy E
Background: Preference-based measures of health-related quality of life (HRQL) are used as primary or secondary endpoints in multiple sclerosis (MS) research. Objective: The purpose of this paper was to evaluate the structural, convergent, and known-groups validity of the preference-based multiple sclerosis index (PBMSI) of HRQL in people with MS. Methods: Participants were recruited from three MS clinics in Montreal. Structural validity was assessed using polychoric correlation coefficients and factor analysis. To assess convergent validity, hypotheses were formulated about the strength of correlations between the PBMSI and other HRQL measures. Known-groups validity was assessed against different measures of disability. Results: The average age of the sample was 46 and 77% were women. Factor analysis supported the structural validity of the PBMSI; the items collectively were measuring one underlying construct. The PBMSI showed convergent validity against generic measures of HRQL, and known-groups validity between persons with different levels of disability. Conclusion: The results of this study support the construct validity of the PBMSI as an outcome measure of HRQL in MS. The PBMSI overcomes limitations observed with currently used HRQL measures in MS and may be used to contrast different interventions for people with MS.